KONSEP PENDIDIKAN AQIDAH PERSPEKTIF ISLAM (Studi Tafsir Tarbawi) - Desi Oktarianti (Conciencia, 2014)
AbstractThis thesis titled Concept of Education Aqeedah Muslim perspective (tarbawi commentaries, motivated by the social phenomenon of many cult. Next of several books / journals known yet many are researching Concept Interpretation Education Perspectives Tarbawi Aqeedah. Islamic Studies are still many who use books contemporary in general. References used are still many who cite the non-Muslim scholars (Orientalist). Therefore, this study raises issues about human nature, the essence of education, Islamic education system and the education system according to the Tafsir Tarbawi aqidah. it aims to to know what is the nature of man, the nature of education, Islamic education system, and the education system aqeedah Tarbawi Tafsir perspective.The approach of this thesis research was Tafsir Tarbawi, namely analyzing passages in connection with education by using content analysis as a means of adjustment. The steps are as follows: Data Reduction Data Display, Conclusion Drawing / Verification by Comparison.From the data analysis it can be concluded that the essence of man in view tarbawi interpretation can be categorized into seven concepts, namely: Abd Allah, Children of Adam, al-Bechar, al-Insan al-Ins, al-Nas, Caliph of Allah. Islamic education system in perspective Tarbawi Commentary consists of: The goal become pious man. Educators God, the Prophets, parents, Gabriel. Learners, the Prophets, Companions, mankind. The curriculum Ideal Curriculum, Actual Curriculum, Curriculum Activity. The method is lecture, exemplary, commands and prohibitions, question and answer, discussion, assignments, stories, proverbs, demonstrations. Media media writes, natural objects, animals, plants. Evaluation al-Inba ', al-reckoning, al-Bala', al-Imtihan. Its environment family, school, community. The source of the Qur'an, Hadith, history, ijtihad scholars. While the Education System in Perspective Commentary Tarbawi creed consists of: The goal is to make people always worship Him. Educators God, the Prophets, parents, Gabriel. Learners of the Prophet, the Companions, mankind. The curriculum Tawheed, Faith, Islam, issues ghaibiyyat, prophetic, destiny, news, danger shirk, kufr, nifaq. The method is exemplary, advice, dialogue, argument, parable, lectures, observation. Media heaven, earth, mountains, stars, animals, stick, palace, al-Quran. Evaluation trials, al-Imtihan in propaganda and maintain Aqeedah especially the Prophets and Messengers, the people of God. Its environment family, mosques / places of worship, schools, social / community. The sources are the Qur'an, Hadith, History. Keywords: Concepts, Education Aqeedah, Tafseer Tarbawi.